Home-use transcranial direct current stimulation (tDCS) as a safe, effective, and feasible application in depression: A randomized, single-blind, placebo-controlled trial - Tuba Aktürk; Mehmet Yücel Ağargün; Sümeyye Özdemir; Esra Dalmızrak; Bahar Güntekin (Journal of Affective Disorders Reports)
Introduction: Anodal transcranial direct current stimulation (tDCS) targeting the left dorsolateral prefrontal cortex (DLPFC) alleviates depression symptoms and enhances cognitive functions in major depressive disorder (MDD) patients. Previously, these outcomes were demonstrated primarily in clinical or laboratory settings through randomized placebo-controlled trials. Our objective was to assess the feasibility and effectiveness of asynchronously supervised, home-use tDCS on both mood and cognition in MDD patients, within a randomized, single-blind, placebo-controlled trial. Method: Twenty MDD patients were randomized into active (N = 11) and sham (N = 9) tDCS groups. The protocol entailed daily 30-minute sessions at 2 mA with the anode over the left-DLPFC and the cathode over the right-DLPFC, conducted five days a week for three weeks. Sham stimulation consisted of a brief 30-second interval between 10-second ramp-up and down periods. After initial training, patients were administered tDCS at home and were evaluated using depression-related questionnaires and cognitive tests at baseline and post-intervention. Adherence and tolerance were asynchronously monitored via a remote supervision platform. Results: High tolerability (adverse-event incidence rate of 0.63 %) and strong adherence (an average of 14.45 out of 15 sessions completed) were observed for home-use tDCS. The active group demonstrated significantly greater improvements in depression scores (BDI-II) and in cognitive performance (Digit Span tests), compared to the sham group, which received placebo treatment with the same protocol. Conclusion: The results of our study demonstrate that home-use tDCS is feasible, safe and might be effective for patients with depression, offering a more accessible and cost-effective approach to neuromodulation treatments in mental health.